2018
DOI: 10.1007/s00285-018-1219-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the potential impact of limited public health resources on the spread and control of typhoid

Abstract: Typhoid fever is a systemic infection caused by Salmonella Typhi and occurs predominantly in association with poor sanitation and lack of clean drinking water. Despite recent progress in water and sanitation coverage, the disease remains a substantial public health problem in many developing countries. A mathematical model for the spread of typhoid has been formulated using non linear ordinary differential equations. The model includes a special treatment function to assess the effects of limited treatment res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…The analysis of the model aims to obtain the positivity and boundedness of the solution, the disease-free equilibrium point, the disease equilibrium point, and their local stability, as well as global stability [46]. The other analysis, such as backward bifurcation [43,45,[51][52][53] and forward trans-critical bifurcation in [50] was carried out in their articles. The optimal control theory was used to analyze the optimal control condition considering the control cost [19,50,55,57].…”
Section: Systematic Literature Review Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of the model aims to obtain the positivity and boundedness of the solution, the disease-free equilibrium point, the disease equilibrium point, and their local stability, as well as global stability [46]. The other analysis, such as backward bifurcation [43,45,[51][52][53] and forward trans-critical bifurcation in [50] was carried out in their articles. The optimal control theory was used to analyze the optimal control condition considering the control cost [19,50,55,57].…”
Section: Systematic Literature Review Resultsmentioning
confidence: 99%
“…The mathematical model for typhoid disease was developed by considering various interventions to control the disease and reduce infection risk. The intervention used most in controlling the disease is treatment [3,18,43,47,50,53,55,57]. Based on some research, treatment is confirmed as the best intervention in controlling the spread of typhoid disease.…”
Section: Systematic Literature Review Resultsmentioning
confidence: 99%
“…The relationship between healthcare and vaccines is bidirectional, as healthcare impacts the dynamics of infectious diseases in the early stage of their encounter, while vaccines include long-term goals. In this regard, some mathematical modelers have put their efforts to study the impact of healthcare facilities or vaccination on disease dynamics [1,2,6,7,8,9,10,11,12,13,14,15,16,19,20,21,22,24,26]. In particular, Abdelrazec et al [1] proposed a deterministic model for the study of dengue fever transmission dynamics as well as the impact of available healthcare resources on the spread and control of disease.…”
Section: Introductionmentioning
confidence: 99%
“…Some models specifically address direct human-to-human transmission [10][11][12], while others incorporate the contribution of indirect transmission through contaminated food and water [13,14]. Some comprehensive models consider both direct and indirect modes of transmission [15][16][17], providing a more complete understanding of the spread of typhoid fever. These models have been instrumental in evaluating the impact of interventions such as disease treatment [14,18], sanitation measures [19,20], education campaigns [21,22], and media coverage [23] on preventing typhoid outbreaks.…”
Section: Introductionmentioning
confidence: 99%